Parents’ perceived knowledge and beliefs on congenital malformations and their causes in the Amhara region, Ethiopia. A qualitative study - Molla Taye (Public Library of Science (PLoS), 2021)
Introduction Knowledge and beliefs of people on congenital malformations and their causes differ from society to society. As a result, there is a paucity of understanding community perceived knowledge and beliefs towards congenital malformations and their risk factors among children’s parents. Therefore, I sought to identify perceived knowledge and beliefs of parents on congenital malformations and their causes. Methods An in-depth discussion and interview were carried out on purposively selected forty participants (women and men) in the Amhara region, Ethiopia. The data were collected from June to July, 2015. Semi-structured guiding topics/questions were used during the discussions and in-depth interviews. Note and audio records were taken while the participants discussed the topics. After the discussions and in-depth interviews were completed, the transcripts were read repeatedly to understand the participant’s words, phrases, ideas, and concepts. Then notes were taken to combine pieces of similar transcripts. I have employed thematic framework analysis. The relevant transcripts were scrutinized, labeled and coded manually based on their relevance to the objective of the study. Then the coded transcripts were determined and categorized according to the type of thematic variables. Results The participants responded on three aspects of lived experience, perceived knowledge and beliefs on congenital malformations and their causes. Nearly half of the participants’ beliefs on the causes of congenital malformations were related to sin, contraceptive pills, un-prescribed drugs/medication use, and fertilizers (that is eating crops grown by using fertilizers). Almost all said that raising a child with a major congenital malformation was very difficult. About half of the participants’ belief on congenital malformations were traditional and resulted from poor awareness. Conclusion The findings of the present study highlight the challenges and impacts of congenital malformations on parents who had children with and without congenital malformation. Lived experience, perceived knowledge and beliefs of children parents on congenital malformation and their causes can be helpful information for designing preventive actions. Hence, planning a preventive strategy and providing health education on congenital malformations and their causes for children parents are very necessary.